The Implementation of the Mental Health Integrated Service Post(Posyandu Jiwa): Mental health training and support for cadres at theCommunity Health Center Level: Implementasi Posyandu Jiwa: Pelatihan dan pendampingan KaderKesehatan jiwa di Tingkat Puskesmas - Buanasari, Andi; Wetik, Syenshie Virgini; Rahman, Asep (Universitas Lancang Kuning, 2025)
The issue of mental health has recently become a prominent topic due to its significant impact. Various efforts have been undertaken, including the establishment of community-based mental health services such as Posyandu Jiwa (Mental Health Integrated Service Post). This community service involves health cadres from the Tikala Baru Public Health Center as partners, aiming to implement Posyandu Jiwa through training and mentorship for mental health cadres. Activities began with socialization, followed by training on mental health screening using SRQ (Self-Reporting Questionnaire) and SDQ (Strengths and Difficulties Questionnaire), along with the stages involved in the implementation of Posyandu Jiwa, culminating in the actual implementation of Posyandu Jiwa. Following the training, there was a notable increase in the knowledge levels of the cadres. Prior to training, 73.3% of cadres were categorized as having limited knowledge, which reduced to only 15.6% post-training. Additionally, there was an improvement in the skills required for conducting screenings, with an average skill score of 76.35 after training. The Posyandu Jiwa was conducted using a five-table system, with cadres stationed at each table and supported by Nurses.